Refining the inventory of the vascular flora of Italy: Unconfirmed, doubtful, excluded or extinct taxa - Domina, Gianniantonio; Abeli, Thomas; Alessandrini, Alessandro; Angiolini, Claudia; Argenti, Carlo; Astuti, Giovanni; Bacchetta, Gianluigi; Bagella, Simonetta; Ballelli, Sandro; Banfi, Enrico; Barberis, Giuseppina; Barone, Giulio; et al. (Phytotaxa, 2025)
The study of a country’s flora is an open-ended work influenced by environmental changes, advances in taxonomical research, and the development of new data collection methods. In Italy, floristic research has evolved from early botanical records to digital databases allowing real-time updates. This study, conducted within the Italian Botanical Society, aimed at verifying, updating and expanding knowledge on species with uncertain, extinct, or excluded status. Starting in 2021, researchers from all regions of Italy collaborated to review literature, herbarium specimens, and field data. Their efforts culminated in 839 regional-level assessments of 628 taxa, leading to 276 changes in regional status and 25 at the national level. These updates are of great significance for nature conservation efforts by confirming species presence in some regions while verifying extinctions, particularly in fragile aquatic habitats. This research also underscores the importance of botanical collections and historical records to reconstruct the history, dynamics, and current distribution of plant species, and addresses challenges such as limited access to the collections. This study is not only a milestone in Italian floristics but also provides a replicable methodology for updating national floras globally.